Pleomorphic xanthoastrocytoma, case series and review of literature - Farrag Mohammad; Ahmed Abd Essattar Abd Elhakeem; Ahmad Algheriany; Ahmed Elshanawany (Egyptian Journal of Neurosurgery)
Abstract Background Pleomorphic xanthoastrocytoma is a rare circumscribed astrocytic glial neoplasm that represents less than 1% of astrocytic tumors. This is a retrospective descriptive hospital-based study of this rare tumor that includes five patients. Epidemiologic characteristics and preoperative clinical findings were recorded. Preoperative MRI characteristics and postoperative histopathology and immunohistochemistry were analyzed. Results The study included five patients, two diagnosed as Pleomorphic xanthoastrocytoma grade 2 tumors and three patients diagnosed as Pleomorphic xanthoastrocytoma grade 3 tumors. Age ranged from 4 to 47 years, three females and two males. All cases presented with seizures, only one case showed neurological deficit. The solid portions showed hyperintense signal in diffusion-weighted image in three cases (Pleomorphic xanthoastrocytoma grade 3), while two cases showed isointense signal (Pleomorphic xanthoastrocytoma grade 2). The mean apparent diffusion coefficient was 0.76 × 10–3 mm2/sec and 1.005 × 10–3 mm2/sec, respectively. Regarding immunohistochemistry, cytoplasmic glial fibrillary acidic protein was strongly positive in all five cases as well as synaptophysin. IDH was negative in all cases. CD34 was positive in three cases, P53 was positive in three cases (Pleomorphic xanthoastrocytoma grade 3), Ki67 was positive in three cases (Pleomorphic xanthoastrocytoma grade 3). Conclusion Pleomorphic xanthoastrocytomas are rare neoplasms with a better prognosis in grade 2 than grade 3. Diffusion-weighted imaging technology can be used to differentiate between grade 2 and grade 3 Pleomorphic xanthoastrocytoma preoperatively but further studies on larger samples are needed to confirm the possibility. Mitotic count is the main parameter used to differentiate Pleomorphic xanthoastrocytoma grade 2 and grade 3, but immunohistochemistry can play a role in that in the future.